2008
DOI: 10.1002/j.0022-0337.2008.72.9.tb04572.x
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Development for Dental Students: What Do Students Think?

Abstract: Effective leaders are needed to move the dental profession forward, building on past accomplishments, meeting new challenges, and leading innovation and change. There is a lack of research findings regarding students' perceptions of the importance of leadership abilities and/or their interest in developing leadership skills during their dental school experience. The purpose of this study was to explore dental students' perceptions related to leadership development. A forty-seven-question, self-administered, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 9 publications
3
56
1
2
Order By: Relevance
“…Even though much leadership research has been undertaken in the nursing and medical professions [e.g. [1][2][3][4][5] there are only a few studies focusing on dentist leaders or leadership in dentistry [6][7][8][9][10][11][12][13][14]. Even fewer studies deal with factors influencing on dentist leaders´ career decisions [6,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Even though much leadership research has been undertaken in the nursing and medical professions [e.g. [1][2][3][4][5] there are only a few studies focusing on dentist leaders or leadership in dentistry [6][7][8][9][10][11][12][13][14]. Even fewer studies deal with factors influencing on dentist leaders´ career decisions [6,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, half of the students recognize in themselves characteristics of leadership. In dentistry, a lot of studies have been focused on the effect of leadership in this career, which showed that most students want to play a leading role in their professional career or in the community where they live 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the exercise of management and a leadership role in dentistry are extremely important in meeting new challenges and leading innovations and changes 1 . The literature shows the importance of the awareness of leadership in various aspects of dentistry, whether it be in clinical practice, in Dental education, research, or in public health [2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of leadership in the oral health profession has been emphasised by the American Dental Association’s report addressing its role. Additionally, leadership development is strongly recommended to be included in dental education.…”
Section: Introductionmentioning
confidence: 99%